TINGKAH LAKU MAKAN IKAN KERAPU MACAN (Epinephelus fuscoguttatus) TERHADAP PERBEDAAN UMPAN (SKALA LABORATORIUM) - Aristi Dian Purnama Fitri (LPPM Universitas Pekalongan, 2011)
Fish eating behavior is the result of the interaction of several senses in fish depend on the habitat and the effect produced by the food. Bait as food is one form of the stimulus in the form of physical / chemical that can provide a response to fish of certain fish for fishing. This study describes the eating behavior of Tiger Krapu Fish (Epinephelus fuscogutattus) by using natural bait during the day and evening. Parameters that observed are patterns of eating behavior and eating response time of Krapu Fish. The research method used is descriptive and experiment on laboratory scale. The Observation of behavioral responses by using a light condition pond and the dark condition pond. Bait that used was a natural bait, including shrimp, fish, and sea urchins. Stages of eating behavior observations including arousal, searching, and finding phase. The behavior of Krapu fish to bait in bright conditions is not different to arousal phase and finding phase. The behaviour of Krapu fish in dark condition to natural bait (sea urchin gonadal, shrimp, and fish) is nit different to arousal phase, searching phase, and finding phase.Keywords : eating behaviour, epinephelus fuscoguttatus), bait